P217 Multi-dimensional assessment and outcomes of dysfunctional breathing (DFB) in a specialist physiotherapy intervention. (12th November 2019) - Paramasivan, C; Knolle, M; Gore, R; Owen, C; Fuld, J
Abstract : Introduction: Physiotherapy led breathing retraining has been reported as effective in dysfunctional breathing. Literature has been emerging about classification, multidimensional assessment and physiotherapy management of DFB. However limited data exists on the effectiveness or consensus on the use of assessment tools. Methods: Patients were referred to specialist respiratory physiotherapy clinic following diagnosis of DFB during Cardiopulmonary exercise testing (CPET) or clinically by respiratory consultants. Physiotherapy training focussed on education about CPET findings and multi dimension of DFB (biomechanical, psychological, and pathophysiological). Techniques included breathing control using nose and abdominal breathing, reducing respiratory rate (RR), improving respiratory volume and expiratory pause and relaxation. Nijmegen and hospital anxiety and depression scale (HADS) questionnaire, respiratory rate (RR) and inspiratory breath-hold (BH) were measured pre- and post-intervention. 25 patients who undertook 2–3 physiotherapy sessions with outcome assessments were included in the data analysis. 12 patients (48%) were female and 13 patients (52%) were male. 16 patients (64%) had prior diagnostic CPET. Pre and post intervention comparison was undertaken using Wilcoxon Signed Ranked Test. Subjects were classified as having responded to individual assessments if either the minimal clinical important difference(MCID) was reached (1.7 HADS) or categorisation became as normal (RR less 16, BH >30 seconds, Nijmegen <23). Results: For the group, RR decreased from 18.16±3.97 to 15.04±1.88 breaths per minute (P<0.01).BH improved from 11.28±7.35 to 23.84±8.79 seconds (P<0.01).Nijmegen scores changed from 27.84±9.67 to 20.64±10.72 (P<0.05).HADS-A changed 9.04±5.19to 7.32±4.75 (P>0.05).HADS-D changed 7.68±4.49 5.68±4.24 (P<0.05). Individual assessment response for each subjects are shown in figure 1. Discussion: DFB physiotherapy intervention is an effective therapy demonstrating improvements in recognised measures. Individual patients may respond in one or more of the assessment tools used to quantify DFB. However, responses may vary across individual assessment tools. No single assessment tool predicts outcomes from intervention. Conclusion: Outcome assessment tools for DFB used in isolation are unlikely to pick up response to therapy in a high proportion of patients. There is a need to develop outcome tools that encompass the varying domains of DFB.